2011
DOI: 10.1103/physreva.84.051402
|View full text |Cite
|
Sign up to set email alerts
|

Optically induced conical intersections in traps for ultracold atoms and molecules

Abstract: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full D… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Another possibility for bridging the 1 mK -1 µK temperature gap is to immerse a gas of molecules into a buffer gas of already ultracold atoms. The calculations by Hutson and coworkers [649,657,658] demonstrated that alkalineearth metal atoms, being structureless and therefore weakly interacting, can be used for sympathetic cooling of molecules such as NH. Interestingly, Tscherbul and coworkers [672] have recently found that sympathetic cooling may work even with alkali metal atoms, such as Li, despite their propensity to generate strongly attractive and anisotropic interactions with molecules.…”
Section: A Towards Ultracold Moleculesmentioning
confidence: 99%
“…Another possibility for bridging the 1 mK -1 µK temperature gap is to immerse a gas of molecules into a buffer gas of already ultracold atoms. The calculations by Hutson and coworkers [649,657,658] demonstrated that alkalineearth metal atoms, being structureless and therefore weakly interacting, can be used for sympathetic cooling of molecules such as NH. Interestingly, Tscherbul and coworkers [672] have recently found that sympathetic cooling may work even with alkali metal atoms, such as Li, despite their propensity to generate strongly attractive and anisotropic interactions with molecules.…”
Section: A Towards Ultracold Moleculesmentioning
confidence: 99%
“…In addition, with the ready availability of laser-cooled atoms there is also a growing interest in these concepts applied to ultracold atom–atom collision. 16 18 The dramatic effect of the light-induced conical intersection on the photodissociation and photofragmentation of the D 2 + molecule was demonstrated in refs ( 19 21 ). Recently, Csehi et al 22 , 23 in theoretical studies showed that LICI in diatomics can be created even by quantized radiation field in an optical cavity.…”
Section: Introductionmentioning
confidence: 80%
“…Study of the core excited CO* molecule in X-ray regimes , show that LICIs should lead to nonadiabatic transitions between electronic, vibrational, and rotational degrees of freedom of the diatomic molecule. In addition, with the ready availability of laser-cooled atoms there is also a growing interest in these concepts applied to ultracold atom–atom collision. The dramatic effect of the light-induced conical intersection on the photodissociation and photofragmentation of the D 2 + molecule was demonstrated in refs . Recently, Csehi et al , in theoretical studies showed that LICI in diatomics can be created even by quantized radiation field in an optical cavity.…”
Section: Introductionmentioning
confidence: 99%
“…1 In order to understand the prospect of cooling trapped molecules to ultralow temperatures, many authors have recently studied the effects of external fields on molecular collisions and chemical reactions. [70][71][72][73][74][75][76][77][78][79][80][81][82][83][84][85][86][87][88] Pioneering experimental studies explored the dynamics of inelastic spin relaxation of magnetically trapped molecular radicals CaH 5,6 and NH 36,37 colliding with background He atoms in a cryogenic environment, and more recent experiments observed cold N-NH, 4 OH-OH, 70 OH-ND 3 , 3 and Rb-ND 3 60 collisions in co-trapped atom-molecule and molecule-molecule ensembles. 4 An exothermic chemical reaction has been observed to occur in an ultracold gas of KRb molecules at temperatures below 1 µK.…”
Section: Introductionmentioning
confidence: 99%